A coupled thermo‐mechanical inelastic analysis approach for reinforced concrete flexural members during fire. (15th December 2017) - Lakhani, Hitesh; Sharma, Akanshu; Hofmann, Jan
Abstract : A practical approach to evaluate the complete load–deflection–time response of reinforced concrete (RC) flexural members under fire is presented. The proposed approach is extendable for performance evaluation of RC structures at all three levels of complexity, namely member level, sub‐assembly level, and the structural level. The approach involves three main steps: (a) transient heat transfer analysis to evaluate the temperature distribution across the critical section; (b) determination of moment–curvature characteristics for the critical sections using temperature‐dependent constitutive laws for concrete and steel; and (c) nonlinear static analysis to obtain load–deflection plots of the member at regular intervals of the fire exposure. The series of load–deflection plots for different exposure durations are then used to obtain the deflection–time plots for the applied load level. The important issue of considering the initial stiffness of fire‐affected beams taking into account the material degradation and thermal damage has been addressed in a simple yet rational manner. The presented approach does not consider the phenomenon of thermal spalling (explosive) and is applicable for cases where thermal spalling can be neglected. The approach is straightforward and easy to implement as only simple tools available to structural design engineers/design offices are required.